Strategi Pemasaran Chocolajit Sebagai Inovasi Pengembangan Makanan Khas Cililin Kabupaten Bandung - Rendi, Rendi; Gunawan, Gunawan (Peneliti.net, 2025)
This study aims to analyze the marketing strategies applied by Chocolajit in developing its product that combines the distinctive taste of Wajit Cililin with chocolate. The study focuses on the aspects of product, price, promotion, and distribution channels. The approach used in this research is qualitative with Analytical Descriptive research method. Data collection methods include interviews, observations, questionnaires, and document analysis to gain a comprehensive understanding of Chocolajit's marketing strategies. The results show that Chocolajit's marketing strategy as an innovation in developing the signature food of Wajit Cililin in Kabupaten Bandung Barat is a deliberate and focused step. The product strategy, covering aspects of innovation, production processes, and product quality, demonstrates Chocolajit's commitment to providing unique and high-quality culinary experiences to consumers. Diverse pricing, promotion, and distribution strategies also play a crucial role in expanding market share and building customer loyalty. Thus, Chocolajit's overall marketing strategy aims not only to achieve business success but also to promote the sustainability of local culture and provide added value to the community. However, there is still potential to enhance collaboration with local traders and pricing flexibility to increase accessibility to Chocolajit products in the market. This research is expected to provide valuable insights for Chocolajit and other food industry players in developing more effective and sustainable marketing strategies.